Ocular larva migrans: a case report. Issue 5 (May 1987) - Lyness, R W; Earley, O E; Logan, W C; Archer, D B
Abstract : A case of intraocular toxocara larva migrans occurring in a 12-year-old boy is presented. Motility is inferred from the nature of multiple intraocular lesions observed. Possible mechanisms preventing a conclusive immunological response to the organism are discussed.